2020
DOI: 10.1093/jamia/ocaa169
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experiences of self-injurious behavior in autism spectrum disorder: Implications for monitoring technology design

Abstract: Objective Monitoring technology may assist in managing self-injurious behavior (SIB), a pervasive concern in autism spectrum disorder (ASD). Affiliated stakeholder perspectives should be considered to design effective and accepted SIB monitoring methods. We examined caregiver experiences to generate design guidance for SIB monitoring technology. Materials and Methods Twenty-three educators and 16 parents of individuals with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, reflections are anticipated about the individual sensory preferences of each person that may compromise the use of SWS in some people with ASD. Themes similar to this one emerged from a previous focus group related to the design of wearable technologies for people with ASD (Cantin-Garside et al, 2021). Furthermore, concerns can arise related to the hottest times of the year, when wearing a tank top under the shirt may be inappropriate.…”
Section: Focus Groupmentioning
confidence: 87%
See 1 more Smart Citation
“…However, reflections are anticipated about the individual sensory preferences of each person that may compromise the use of SWS in some people with ASD. Themes similar to this one emerged from a previous focus group related to the design of wearable technologies for people with ASD (Cantin-Garside et al, 2021). Furthermore, concerns can arise related to the hottest times of the year, when wearing a tank top under the shirt may be inappropriate.…”
Section: Focus Groupmentioning
confidence: 87%
“…Moreover, higher prediction performance was reported for the SVM + PCA model than for the LR model. Consistently, Cantin-Garside et al (2021) reported higher accuracy of SVM and k-nearest neighbor (kNN) algorithm in classifying self-injurious behavior in children with ASD compared to other methods [discriminant analysis (DA), decision trees (DT), Naïve Bayes (NB), and neural networks (NN)]. Furthermore, Zheng et al (2021) proposed a multimodal data analysis to predict precursors of CBs of children with ASD through various ML algorithms.…”
Section: Introductionmentioning
confidence: 89%
“…The objective of 90% of the research paper [11-14, 18, 20, 21, 49, 79, 95-97] is to detect ASD by ML and IoT. Only 9% researchers [29,94,98,99] focused on the study and analysis of self-Injurious Behavior of Autistic children. The rest of the paper [100,101] focuses on detecting and monitoring the child's hyperactivity .…”
Section: Q3 Which Technique Is Used To Assess the Provided Technologi...mentioning
confidence: 99%
“…On the other hand, Garside et al [99] recruited 11 ASD children with their caretakers for the SIB database. They used a multilevel logistic regression model for group-level SIB classification.…”
Section: Self-injurious Behaviour (Sib) Detectionmentioning
confidence: 99%
“…There is some evidence for a positive association (Samson et al, 2014) between SIB and emotion dysregulation, while other work reports a negative relationship between SIB and anxiety severity (Williams et al, 2015). A recent qualitative study interviewing caregivers of autistic individuals about their children's SIB found that emotional responses-most often consisting of feeling upset, stressed, frustrated, or angry-emerged as a prominent theme in discussing caregivers' perceptions of direct causes of SIB (Cantin-Garside et al, 2021).…”
Section: Introductionmentioning
confidence: 99%